Continuous block-symmetric polynomials of degree at most two on the space $(L_∞)^2$ - Vasylyshyn, T.V. (Carpathian Mathematical Publications, 2016)
We introduce block-symmetric polynomials on $(L_∞)^2$ and prove that every continuous block-symmetric polynomial of degree at most two on $(L_∞)^2$ can be uniquely represented by some "elementary" block-symmetric polynomials.